2015
DOI: 10.1016/j.cortex.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical volumetric changes across the adult lifespan: Subregional thalamic atrophy accounts for age-related sensorimotor performance declines

Abstract: Even though declines in sensorimotor performance during healthy aging have been documented extensively, its underlying neural mechanisms remain unclear. Here, we explored whether age-related subcortical atrophy plays a role in sensorimotor performance declines, and particularly during bimanual manipulative performance (Purdue Pegboard Test). The thalamus, putamen, caudate and pallidum of 91 participants across the adult lifespan (ages 20-79 years) were automatically segmented. In addition to studying age-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 67 publications
(103 reference statements)
5
30
0
Order By: Relevance
“…For example, a reduction in thalamic volume along the lifespan has been associated with age-related sensorimotor performance deterioration (Serbruyns et al, 2015). In relation to BG, and far beyond its classical association to motor function (Kandel, Schwartz, Jessell, Siegelbaum, & Hudspeth, 2012), there is nowadays mounting evidence to associate the BG decline with executive function deficits along the lifespan, such as motor switching (Coxon et al, 2010), inhibitory , and cognitive control (Grady, 2012), but also learning (Chalavi et al, 2018), whereby older adults perform worse than young.…”
Section: Differences Between Brain Age and Cha By Assessing Brain Mmentioning
confidence: 99%
“…For example, a reduction in thalamic volume along the lifespan has been associated with age-related sensorimotor performance deterioration (Serbruyns et al, 2015). In relation to BG, and far beyond its classical association to motor function (Kandel, Schwartz, Jessell, Siegelbaum, & Hudspeth, 2012), there is nowadays mounting evidence to associate the BG decline with executive function deficits along the lifespan, such as motor switching (Coxon et al, 2010), inhibitory , and cognitive control (Grady, 2012), but also learning (Chalavi et al, 2018), whereby older adults perform worse than young.…”
Section: Differences Between Brain Age and Cha By Assessing Brain Mmentioning
confidence: 99%
“…Similarly, a DTI study of 121 participants (aged 18–61 year) observed that motor task performance was negatively associated with thalamo‐precentral gyrus connectivity (radial diffusivity), while better verbal memory scores were positively associated with the number of thalamic voxels characterized as being “connected” to frontal, parietal, and temporal ROIs (Philp, Korgaonkar, & Grieve, 2014). Furthermore, gross morphometric alterations to the thalamus with advanced age have also been reported (Goodro, Sameti, Patenaude, & Fein, 2012; Long et al., 2012; Serbruyns et al., 2015; Sullivan, Rosenbloom, Serventi, & Pfefferbaum, 2004), although not universally (Good et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, aging may interact with the coordination effect we reported earlier. On a neurobiological level, Serbruyns et al (2015) have shown an age-related volumetric decline in the putamen, pallidum, and caudate. The interaction between age and complexity may be better reported by RT than error data.…”
Section: Introductionmentioning
confidence: 99%